Anti-inflammatory activity of An Ethanol Extract of Pucuk Merah (Syzigium myrtifolium Walp.) in vivo - Nursyafni, Nursyafni; Rahmawati, Ayu; Indriani, Lusi; Ashari, Dicki Hamed (Fakultas Farmasi Universitas Andalas, 2023)
Compared with classical Utilization of medicinal plants with anti-inflammatory properties, it needs to be done to find alternative treatments with relatively more minor side effects, such as Syzygium myrtifolium walp. This study aims to determine the effective dose of ethanol extract of pucuk merah as an anti-inflammatory in 30 male white rats of the Wistar strain. Testing the extract's anti-inflammatory effect was measured by measuring the edema volume on the soles of the rats' feet after being induced with 1% carrageenan with a pletismometer. The test animals were divided into six treatment groups, namely group 1 negative control (Na CMC 1%), group 2 positive control (Na Diclofenac 50 mg/KgBW), group 3 (dose of pucuk merah leaves extract 75 mg/KgBW), group 4 (quantity of pucuk merah leaves extract 100 mg/kgBW), and group 5 (amount of pucuk merah leaves extract 125 mg/kg BW), with observation times of 30, 60, 90, 120, 150, and 180 minutes. The results showed that rats in group 5 with a dose of pucuk merah (125 mg/kgBW) had the best anti-inflammatory effect, with an anti-inflammatory potential of 97% compared to diclofenac sodium.